Psoralens activate and photosensitize Transient Receptor Potential channels Ankyrin type 1 (TRPA1) and Vanilloid type 1 (TRPV1) - Babes, Alexandru; Kichko, Tetyana; Selescu, Tudor; Manolache, Alexandra; Neacsu, Cristian; Gebhardt, Lisa; Reeh, Peter (European Journal of Pain, 2020)
Background: PUVA (psoralen UVA) therapy is used to treat a variety of skin conditions, such as vitiligo psoriasis, eczema and mycosis fungoides, but it is frequently accompanied by phototoxicity leading to burning pain, itch and erythema. Methods: We used a combination of calcium and reactive oxygen species (ROS) imaging, patch clamp and neuropeptide release measurement to investigate whether certain ion channels involved in pain and itch signalling could be responsible for these adverese effects of PUVA. Results: Clinically used psoralen derivatives 8-methoxypsoralen (8-MOP) and 5-methoxypsoralen at physiologically relevant concentrations were able to activate and photosensitize two recombinant thermoTRP (temperature-gated Transient Receptor Potential) ion channels, TRPA1 (Transient Receptor Potential Ankyrin type 1) and TRPV1 (Transient Receptor Potential Vanilloid type 1). 8-MOP enhanced ROS production by UVA light, and the effect of 8-MOP on TRPA1 could be abolished by the antioxidant N-acetyl cysteine and by removal of critical cysteine residues from the N-terminus domain of the channel. Natively expressed mouse TRPA1 and TRPV1 both contribute to photosensitization of cultured primary afferent neurons by 8-MOP, while direct neuronal activation by this psoralen-derivative is mainly dependent on TRPV1. Both TRPA1 and TRPV1 are to a large extent involved in controlling 8-MOP-induced neuropeptide release from mouse trachea. Conclusions: Taken together our results provide a better understanding of the phototoxicity reported by PUVA patients and indicate a possible therapeutic approach to alleviate the adverse effects associated with this therapy. Significance: Our work provides evidence for the involvement of thermoTRP channels TRPA1 and TRPV1 in the activation and photosensitization of peripheral nociceptors during PUVA (Psoralen UVA) therapy.
CRIS-Team Scopus Importer:2020-10-02